Inhibition of monoamine oxidase activity by cannabinoids - Fisar, Zdenek (Naunyn-Schmiedeberg's archives of pharmacology, 2010)
Brain monoamines are involved in many of the same processes affected by neuropsychiatric disorders and psychotropic drugs, including cannabinoids. This study investigated in vitro effects of cannabinoids on the activity of monoamine oxidase (MAO), the enzyme responsible for metabolism of monoamine neurotransmitters and affecting brain development and function. The effects of the phytocannabinoid Delta(9)-tetrahydrocannabinol (THC), the endocannabinoid anandamide (N-arachidonoylethanolamide [AEA]), and the synthetic cannabinoid receptor agonist WIN 55,212-2 (WIN) on the activity of MAO were measured in a crude mitochondrial fraction isolated from pig brain cortex. Monoamine oxidase activity was inhibited by the cannabinoids; however, higher half maximal inhibitory concentrations (IC(50)) of cannabinoids were required compared to the known MAO inhibitor iproniazid. The IC(50) was 24.7 micromol/l for THC, 751 micromol/l for AEA, and 17.9 micromol/l for WIN when serotonin was used as substrate (MAO-A), and 22.6 micromol/l for THC, 1,668 micromol/l for AEA, and 21.2 micromol/l for WIN when phenylethylamine was used as substrate (MAO-B). The inhibition of MAOs by THC was noncompetitive. N-Arachidonoylethanolamide was a competitive inhibitor of MAO-A and a noncompetitive inhibitor of MAO-B. WIN was a noncompetitive inhibitor of MAO-A and an uncompetitive inhibitor of MAO-B. Monoamine oxidase activity is affected by cannabinoids at relatively high drug concentrations, and this effect is inhibitory. Decrease of MAO activity may play a role in some effects of cannabinoids on serotonergic, noradrenergic, and dopaminergic neurotransmission.
Keywords: Monoamine Oxidase; morfoliny; Morpholines; Animals; vztah mezi dávkou a účinkem léčiva; Monoamine Oxidase Inhibitors; tetrahydrokanabinol; Inhibitory Concentration 50; Iproniazid; endokanabinoidy; benzoxaziny; iproniazid; inhibiční koncentrace 50; prasata; mozek; monoaminoxidasa; Polyunsaturated Alkamides; kyseliny arachidonové; Naphthalenes; Dose-Response Relationship, Drug; Endocannabinoids; inhibitory MAO; Brain; Swine; Dronabinol; Benzoxazines; Arachidonic Acids; naftaleny; zvířata; polynenasycené alkamidy